Interfacial stabilizing and reinforcing effects of silsesquioxane-based hybrid Janus molecules in extrusion supercritical CO₂ foaming of polypropylene - Ho, Keen Hoe (2023)
High-melt-strength (HMS) polypropylene (PP) has enabled easy supercritical-CO2 (scCO2) foaming of PP. However, producing microcellular PP foams via simple scCO2 extrusion foaming still remains challenging, whereas macrocellular PP foams with high expansion ratios (ER) generally exhibit poor mechanical strengths. In this study, to simultaneously enhance both ER and compressive strengths of macrocellular PP foams, a type of low-cost Janus molecules, heptaisobutyl open-cage silsesquioxane (HOS), is incorporated into HMS-PP. Since HOS has PP-philic groups and a partially condensed silsesquioxane cage that is relatively CO2-philic, it could diffuse like a surfactant to the PP-CO2 interface during scCO2 extrusion foaming to stabilise the cells in their growth stage and reinforce the cell surface upon solidification. The surfactant effect is validated via X-ray Photoelectron Spectroscopy. Moreover, with 1 wt% HOS, the PP/HOS foam could offer 38 % ER improvement, 23 % density reduction, and 20 % compressive strength increase over the neat PP foam. HOS could also slightly improve the extensional viscosity and melt strength of PP at ≤1 wt% loadings and reduce the shear viscosity of PP by acting as a lubricant. This approach provides a simple and economically viable materials design guideline for alleviating ER-compression strength trade-offs for macrocellular polymer foams.